PERJANJIAN PENGGUNAAN ROOFTOP ANTARA PERUSAHAAN TELEKOMUNIKASI DENGAN PEMILIK BANGUNAN DI KOTA MEDAN - ISKANDAR SAWALEO (PREMISE LAW JURNAL, 2016)
The real form of communication is the use of cellular phone which depends on cellular operator as a telecommunication service provider. To improve its capacity and quality, the operator construct telecommunication tower. The operator constructing a tower on the rooftop of a building makes a lease agreement with the building owner. The agreement was studied two rooftop lease agreements between the operator and the owner of the buildings located in the city of Medan. The problems which arise in the rooftop lease agreement were why the rooftop use agreement is made between the telecommunication company and the building owner in the city of Medan, how this agreement is implemented, what legal protection that can be given to the owner of the building and the community living around the tower constructed as stated in the rooftop use agreement, and what constraint are faced and how to solve them in the implementation of the agreement. Keywords: Agreement, Rooftop, Telecommunication, Building Owner